2010
DOI: 10.1111/j.1432-2277.2009.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of renal ischemia–reperfusion injury by postconditioning involves adenosine receptor and protein kinase C activation

Abstract: Summary Significant organ injury occurs after transplantation and reflow (i.e., reperfusion injury). Postconditioning (PoC), consisting of alternating periods of reperfusion and re‐occlusion at onset of reperfusion, attenuates reperfusion injury in organs including heart and brain. We tested whether PoC attenuates renal ischemia–reperfusion (I/R) injury in the kidney by activating adenosine receptors (AR) and protein kinase C (PKC). The single kidney rat I/R model was used. Groups: (1) sham: time‐matched surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 50 publications
2
26
0
3
Order By: Relevance
“…23 ROS activate a host of pathological processes including DNA damage, protein oxidation and nitrosylation, lipid peroxidation, and induction of apoptosis. 24 Indeed, peroxidation of membrane lipids can disrupt membrane fluidity and cell compartmentalization, which can result in cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…23 ROS activate a host of pathological processes including DNA damage, protein oxidation and nitrosylation, lipid peroxidation, and induction of apoptosis. 24 Indeed, peroxidation of membrane lipids can disrupt membrane fluidity and cell compartmentalization, which can result in cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…More delayed ischemic postconditioning, starting 6 and 24 h after focal and global cerebral ischemia, respectively, has also been described [12]. Studies with ischemic postconditioning (brief interruption of blood flow) leading to amelioration of renal injury have also been reported in animal models of I/R induced AKI [13,14,15,16,17,18]. In most of these studies HIF activation is one of the predominant mechanisms implicated for the observed tissue salvaging effects of postconditioning.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many scientists report that renal I/R injury is a common cause of renal cell death, acute renal failure and, in the case of transplantation, delayed graft function or graft rejection. [2][3][4] Many mediators are involved in the pathophysiology of I/R injury, including reactive oxygen species (ROS), reactive nitrogen species (RNS), purine metabolites, neutrophil accumulation, vasoactive substance (endothelin, angiotensin II) and subsequent release of lytic enzymes.…”
mentioning
confidence: 99%